Atherosclerosis at arterial bifurcations: evidence for the role of haemodynamics and geometry - Morbiducci, Umberto; Kok, Annette M.; Kwak, Brenda R.; Stone, Peter H.; Steinman, David A.; Wentzel, Jolanda J. (Thrombosis and Haemostasis, 2016)
Atherosclerotic plaques are found at distinct locations in the arterial system, despite the exposure to systemic risk factors of the entire vascular tree. From the study of arterial bifurcation regions, emerges ample evidence that haemodynamics are involved in the local onset and progression of the atherosclerotic disease. This observed co-localisation of disturbed flow regions and lesion prevalence at geometrically predisposed districts such as arterial bifurcations has led to the formulation of a ‘haemodynamic hypothesis’, that in this review is grounded to the most current research concerning localising factors of vascular disease. In particular, this review focuses on carotid and coronary bifurcations because of their primary relevance to stroke and heart attack. We highlight reported relationships between atherosclerotic plaque location, progression and composition, and fluid forces at vessel’s wall, in particular shear stress and its ‘easier-tomeasure’ surrogates, i.e. vascular geometric attributes (because geometry shapes the flow) and intravascular flow features (because they mediate disturbed shear stress), in order to give more insight in plaque initiation and destabilisation. Analogous to Virchow’s triad for thrombosis, atherosclerosis must be thought of as subject to a triad of, and especially interactions among, haemodynamic forces, systemic risk factors, and the biological response of the wall.
Keywords: Atherosclerosis; biomechanics; shear stress; arterial bifurcation; haemodynamics